The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.jaci.2019.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E is a concentration-dependent pulmonary danger signal that activates the NLRP3 inflammasome and IL-1β secretion by bronchoalveolar fluid macrophages from asthmatic subjects

Abstract: Background: House dust mite (HDM)-challenged Apoe 2/2 mice display enhanced airway hyperreactivity and mucous cell metaplasia. Objective: We sought to characterize the pathways that induce apolipoprotein E (APOE) expression by bronchoalveolar lavage fluid (BALF) macrophages from asthmatic subjects and identify how APOE regulates IL-1b secretion. Methods: Macrophages were isolated from asthmatic BALF and derived from THP-1 cells and human monocytes. Results: HDM-derived cysteine and serine proteases induced APO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 83 publications
(134 reference statements)
3
41
0
Order By: Relevance
“…( Bonanad et al, 2020 ) Second, patients with dementia were associated with the ApoE e4 genotype. ( Kuo et al, 2020 ) ApoE itself has lipoprotein function and modulates the macrophage pro/anti-inflammatory phenotypes ( Tudorache et al, 2017 ) and is expressed by many cell types in the lung, including macrophages, type I and type II alveolar epithelial cells ( Gordon et al, 2019 ), therefore it is possible that having one or two copies of ApoE4 can increase the risk of having severe COVID-19 infection by robust innate immune response and cytokine storm that results in acute respiratory distress syndrome (ARDS). Third, inflammation also plays an important role in the pathogenesis of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…( Bonanad et al, 2020 ) Second, patients with dementia were associated with the ApoE e4 genotype. ( Kuo et al, 2020 ) ApoE itself has lipoprotein function and modulates the macrophage pro/anti-inflammatory phenotypes ( Tudorache et al, 2017 ) and is expressed by many cell types in the lung, including macrophages, type I and type II alveolar epithelial cells ( Gordon et al, 2019 ), therefore it is possible that having one or two copies of ApoE4 can increase the risk of having severe COVID-19 infection by robust innate immune response and cytokine storm that results in acute respiratory distress syndrome (ARDS). Third, inflammation also plays an important role in the pathogenesis of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…APOE activated the NLRP3 inflammasome and IL-1b secretion from ex vivo cultures of asthmatic alveolar Th1/ILC1 IFN-g, CXCL10, SLPI, TNF chestjournal.org macrophages. 29 APOE also induced the secretion of both CXCL5 and IL-8, which have chemoattractant activity toward neutrophils, by ex vivo cultures of asthmatic airway epithelial cells via a TLR4/TAK1/ IKKb/NF-kB/TPL2/JNK signaling pathway. 35 In conclusion, the identification of biomarkers to distinguish endotypes that mediate neutrophilic asthma can guide the development of targeted interventions that are delivered in a precision medicine approach to those subjects in whom the pathway is active (Table 1).…”
Section: Macrolidesmentioning
confidence: 95%
“…IL-1b is a proinflammatory cytokine generated by the NLRP3 (nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain-containing protein 3) inflammasome, mainly in monocytes and macrophages, and plays a central role in mediating chestjournal.org innate immunity. 29 Both the NLRP3 inflammasome and IL-1b have been linked to neutrophilic airway inflammation and increased disease severity in severe, steroid-resistant asthma. The concept of targeting IL-1b for neutrophilic asthma has advanced to early-stage clinical trials.…”
Section: Il-1bmentioning
confidence: 99%
“… 6 Second, patients with dementia were associated with the ApoE e4 genotype. 7 ApoE itself has lipoprotein function and modulates the macrophage pro/anti-inflammatory phenotypes 8 and is expressed by many cell types in the lung, including macrophages, type I and type II alveolar epithelial cells 9 , therefore it is possible that having one or two copies of ApoE4 can increase the risk of having severe COVID-19 infection by robust innate immune response and cytokine storm that results in acute respiratory distress syndrome (ARDS). A study by Kuo et al 10 has demonstrated that patients with ApoE e4e4 more likely to have severe COVID-19 infections.…”
mentioning
confidence: 99%